Jesus and the Feminine Genius. The Anthropological Relevance of the Encounters of Jesus with Women in the Fourth Gospel - Marc Timmermans (Polonia Sacra, 2019)
Pope John Paul II introduced the expression of the “Feminine Genius” in his Apostolic Letter Mulieris Dignitatem of 1988. If this characteristic belongs to all women in history, there must be traces of it in the Gospel. The article verifies that this is the case in the Gospel of John. Indeed, taking a closer look to the different encounters between Jesus and individual women, we see that the latter have a specific influence on the action of Jesus and participate in a particular way in the mission of Jesus. Two key ideas can help us clarify in which way these women participate in Jesus’ mission. The first is the fruitfulness of faith. Those who believe are born from God himself (1:13), through faith in Christ. This is particularly the case for the Samaritan woman (4:4–42). Her life changes when she comes progressively to faith in Christ: “could he be the Christ?” (4:29). The second key idea is the prophecy of the High Priest Caiaphas: “Jesus was to die for the nation and not for the nation only but also in order to gather into one the scattered children of God.” (11:51–52). Again, the Samaritan woman can serve as an example. She goes back to her town and brings her fellow Samaritans to faith in Jesus (4:39: “Many of that town believed in him”). They represent the first fruits of the great eschatological harvest, the gathering of those who believe in Jesus. Both ideas can shine a light on the specific mission of women in the Fourth Gospel. From Mary in Cana or at the foot of the cross to Mary Magdalene at the tomb, from the Samaritan woman to the adulterous woman and the sisters Martha and Mary, they all influence Jesus in his specific mission of arousing faith and gathering the scattered children of God. These encounters will help us to understand more concretely what John Paul II meant by Feminine Genius and what the role of women in the mission of the Church could be now.